If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -1) + -2(x + 5) = 32 Reorder the terms: 4(-1 + x) + -2(x + 5) = 32 (-1 * 4 + x * 4) + -2(x + 5) = 32 (-4 + 4x) + -2(x + 5) = 32 Reorder the terms: -4 + 4x + -2(5 + x) = 32 -4 + 4x + (5 * -2 + x * -2) = 32 -4 + 4x + (-10 + -2x) = 32 Reorder the terms: -4 + -10 + 4x + -2x = 32 Combine like terms: -4 + -10 = -14 -14 + 4x + -2x = 32 Combine like terms: 4x + -2x = 2x -14 + 2x = 32 Solving -14 + 2x = 32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 2x = 32 + 14 Combine like terms: -14 + 14 = 0 0 + 2x = 32 + 14 2x = 32 + 14 Combine like terms: 32 + 14 = 46 2x = 46 Divide each side by '2'. x = 23 Simplifying x = 23
| sqrt(4z+9)=z+1 | | 8z^3-12z^2+10z-3=0 | | 7x-(8x+8)=x-9 | | 10-3q=1 | | 4(2+3x)=5 | | h=-64t^2+qt+k | | 392*x=49 | | 69x=690 | | 40x+34=634 | | 2x+32=7x+7 | | x(2x+21)=180 | | p(x)=x^2-7x-10 | | x^2+a^2-14x-10a+58=0 | | 4(x-1)+13=x-3(x+1) | | 5+2y=15-3y | | G=9/4(p-1) | | 30=5c+20 | | 15-27b+11=-244 | | 46+X=349 | | 5x-1=2x-5 | | LOG(7)(4-X)=1 | | 3x-14+3x=3+6x-17 | | 15a^2-6ab-8a^2+20-5ab-31+a^2-ab=0 | | LOG(7)4-X=1 | | 10x=9x+21 | | 9y^2+24y+72x+16=0 | | (.2x)+x=40 | | 45x=64x+8 | | 90=2w+2(2w+6) | | 11x=247 | | 5d+10=8d-14 | | (2x-5)(x)=52 |